Preparation of Novel ICT-CMC-CD59sp Drug-Loaded Microspheres and Targeting Anti-Tumor Effect on Oral Squamous Cell Carcinoma - Gao, Xiang; Wang, Wanchun; Gao, Meihua (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of oral squamous cell carcinoma (OSCC) remains a great clinical challenge, and the malignant proliferation of OSCC cells can lead to the overexpression of CD59. In this study, a novel microsphere (ICT-CMC-CD59sp) composed of icariin (ICT), carboxymethyl chitosan (CMC) and cell differentiation antigen 59-specific ligand peptide (CD59sp) were successfully prepared by emulsion cross-linking method. Through the guidance of CD59sp, microspheres can target OSCC cells and play a therapeutic role (P<0.01). MTT test and trypan blue staining showed that the above microspheres could promote the apoptosis of oral squamous cell carcinoma and had significant difference (P<0.01). In this study, the regulatory effect of the microspheres on OSCC cells was investigated at the cellular level, and its therapeutic effect on OSCC was discussed, which provided a new idea for the targeted therapy of OSCC.